Kemahiran mengakses dan mempelajari bahan hiperteks dalam kalangan guru pelatih - Saemah Rahman,; Siti Fatimah Mohd. Yassin, (penerbit ukm, 2008)
Accessing hypertext learning materials from the internet is one of key features in current learning environment. Thus, one of the important skills in this learning environment is the ability to access and study hypertext materials online. This paper discusses the result of a study done to identify student teachers’ skills in accessing and studying hypertext materials online. Respondents of the study consist of 40 first year student teachers at the Faculty of Education in one public university in Malaysia. The respondents were asked to study hypertext materials online. Subsequently, they were asked to answer questions related to hypertext materials and the learning process they had undergone. They were also asked to do metacognitive reflection explaining the steps they used in learning the materials online. Descriptive data were analysed using percentages. Document analysis technique was also employed on the metacognitive reflection report. In addition, analysis was also done on screen interaction of 10 student teachers while accessing and studying the hypertext materials online. Results of the study showed that as a whole, the respondents acknowledged the importance of hypertext materials in their learning process. However, results of the study showed that the respondents still lack of study skills needed in hypermedia learning environment. Majority of the respondents showed very minimal application of metacogitive strategies in accessing and studying the hypertext materials online. The general approach adopted by the respondents is a “cut and paste” approach without an attempt to process or understand the information retrieved. One important implication of this study is the need to train student teachers to use metacognitive strategies to help them learn effectively and consequently able to play their role as a teacher to guide their students learning in hypermedia learning environment.